Pakistan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper provides an overview of social safety nets (SSNs) in Pakistan and uses a frontier analysis approach to assess their efficiency in reducing poverty and inequality. SSNs in Pakistan were significantly strengthened over time but remain small against regional and emerging markets' averages. The analysis suggests that stepping up public expenditure in SSNs is needed to alleviate still high poverty and inequality. To this end, finalizing the update of the Benazir Income Support Program beneficiaries' database, broadening its coverage, and stepping up educational transfers is key. In parallel, continuing the energy subsidies reform would create fiscal space to strengthen SSNs and priority social spending.